PERAN PENGURUS DALAM PENANAMAN KARAKTER KEBANGSAAN SANTRI DI MA’HAD MAMBA’UL QUR’AN MUNGGANG WONOSOBO - Uljaziah, Ulya Rifa; Imron, Ali; Nugroho, Muhammad Yusuf Amin (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2019)
This study aims to determine the role of the board in instilling the national character of the students at the Ma'had Mamba'ul Qur'an Islamic Boarding School, Munggang Wonosobo, to find out the strategy in instilling an attitude of love for the homeland and the spirit of nationalism in the students at the Ma'had Mamba'ul Islamic Boarding School. Qur'an Munggang Wonosobe, to find out the problems in inculcating the national character of students at the Ma'had Mamba'ul Qur'an Islamic Boarding School Munggang Wonosobo. The method in this study uses an approach approach where the type of research is Field Research, namely research that is carried out intensively and specifically on a desired object by studying various data boosters or a supporting case. The researchers used data collection techniques in this study, using interviews, observation and documentation. The results of this study indicate that the role of the board in instilling the national character of the santri in the Ma'had Mamba'ul Qur'an Islamic boarding school in Munggang Wonosobo is the role of a supervisor, the role of the administrator as an educator and also the role of the board as a friend. The strategy for instilling the character of love for the homeland and the spirit of nationalism is through cottage activities, these activities are roan, muhadhoroh, grave pilgrimage. gymnastics, early madrasah, tree planting, flag ceremony. Problems in instilling the national character of the santri in the Ma'had Mamba'ul Qur'an Islamic boarding school Munggang Wonosobo are internal factors and external factors. Internal factors are due to the emergence of a sense of laziness, boredom and also the lack of awareness of students or students' understanding of national character. External factors due to technological advances and also caused by the environment.